Influence Perception Facilities Use, Promotion Cashback, And Trust Towards Interest In Using The OVO Application Among Teenagers In Surabaya - Indriana Kristiawati; Dian Arisanti; Mudayat, Mudayat; Novita Wulandari (Sean Institute, 2024)
This study aims to analyze the influence of perceived ease of use, cashback promotions, and trust on the intention to use the OVO application among teenagers in Surabaya. Using the Technology Acceptance Model (TAM) theory, this research explores three independent variables: the influence of ease of use, cashback promotions, and trust, as well as their influence on the intention to use the OVO application as the dependent variable. This study uses a survey method with questionnaires distributed to 96 teenage respondents in Surabaya. Data analysis was conducted using multiple regression tests. The results show that perceived ease of use, cashback promotions, and trust have a positive and significant influence on the intention to use the OVO application, with t-values of 6.544, 9.862, and 7.494, respectively, all of which are greater than the t-table value of 1.986 at a significance level of 0.000 < 0.05. The three variables also collectively have a significant influence on the intention to use the OVO application, with an F-value of 44.397 greater than the F-table value of 2.70.